GAMBARAN KELUHAN DAN PERAWATAN PASIEN YANG DATANG KE POLIGIGI RSU JATIROTO TAHUN 2010 KISWALUYO - Kiswaluyo Kiswaluyo (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2012)
Cultural advancement of society will be accompanied by an increase in the demands of life. The demands of health, especially dental and oral health is an integral part of health in general and subsequently became one of the keys to the success of national development 1. Indonesia public awareness of the importance of oral health is still relatively low when compared with other countries. The community is still reluctant to health check their teeth, even not a few others who are afraid of seeing a dentist. This led to increasingly complex problems of oral health. Developments in medicine and dentistry in particular have grown so rapidly mouth. Types of care and handling of the increasingly diverse, so the facilities demanded more complete service and integrated. Complaint data on the patients most DJATIROTO RSU 2010 is the patient with dental pulp hyperemia (HP) of 901, pulp gangrene (GP) of 913, gangrene radik (GR) 255, 431 as much persistence, abscesses and gingivitis as many as 468 580. Therapy is the most widely performed on HP gear is a composite material compact and dense glass ionomer (GI), with GP dental root canal treatment with medication and some do the extraction, the tooth with medication and GR is the extraction, the tooth with the persistence of the action extractions, abscesses and open burs with medication and in the case of gingivitis skalling action.